Efeito do nitrogênio na nutrição do girassol - Lobo, Thomaz Figueiredo [UNESP]; Filho Grassi, Helio [UNESP]; Brito, Iere Caindre Andrade (My University, 2011)
Nitrogen (N), besides being one of the macro more absorbed by plants, is the that most limits the production of sunflower. The aim of this study was to evaluate the nutrient content in leaves, grains and nutrient export due to nitrogen levels in sunflower cultivation. A randomized experimental block design consisting of five treatments and four replications: T1 - 50 kg N ha -1 divided by 10, 20 and 20 kg ha -1, T2 - 70 kg N ha -1 divided by 10, 30 and 30 kg ha -1; T3 - 90 kg N ha -1 divided by 10, 40 and 40 kg ha -1, T4 - 110 kg N ha -1 divided by 10, 50 and 50 kg ha -1, T5 - 130 kg N ha- 1 divided by 10, 60 and 60 kg ha -1. These applications were made in installments when sowing and 34 and 48 days after sowing. The parameters were evaluated in leaf nutrient content, nutrient content in grains and nutrient export. Under the experimental conditions it was found that the optimum foliar N were purchased at a dosage above 110 kg ha -1 N. With the increasing amount of N supplied in the sunflower crop was exported over this element, but not at the same rate of increase in dosage. The lowest dose of N the lowest rates of export of P, K, Mg, S, B, Cu, Mn and Zn, while increasing the dose of this nutrient decreased the export of Ca.
Effect of nitrogen nutrition in sunflower
Keywords: Hellianthus annus; N fertilization; Nutrient export